Lifestyle: Flexing Behavior in Social Media - Alton Endarwanto Hadi Susanto; Nadiroh; Hafid Abbas; Agung Purwanto (International Journal of Economics (IJEC), 2023)
Global environmental degradation cannot be separated from people behavior and lifestyle, one of which is the flexing phenomenon. This study was conducted using a qualitative phenomenological approach and explained descriptively because the researcher aimed to obtain an in-depth picture of the flexing phenomenon in society. The results of this study revealed that the flexing phenomenon is actually has been around for a long time, and has now developed in society and has become an arena for showing off people’s wealth and accomplishments. On the conclusion, flexing is often considered as deception because the doer usually doesn’t show his/her reality. Flexing behavior is done by people who want to be recognized that they belong to a higher social status (social climber). This flexing behavior is not only done by the upper class but also by the middle class and the lower class. Usually they do anything to meet the demands of the up-to-date lifestyle. The activity of flexing is not only do directly, but also through social media as well. People are competing to show off the luxury items they have. The flexing phenomenon is associated with structural functionalism, that is, changes that occur which will not change the basic elements of socio-culture